Bancassurance jako forma aliansów strategicznych podmiotów na rynku finansowym - Ratowska-Dziobiak, Eleonora (Gospodarka w Praktyce i Teorii, 2011)
The aim of this article is an attempt to present the bancassurance, its causes, forms and directions of development, both in Poland and Western Europe, with particular emphasis on the objectives to be pursued through the implementation of a strategy to provide integrated financial services. The analysis was performed by taking into account the current global economic situation and trends in the banking and insurance sector.